Towards an emerging role for anticoagulants in cancer therapy: a systematic review and meta-analysis - Al-Azzawi, Huda Moutaz Asmael; Hamza, Syed Ameer; Paolini, Rita; Arshad, Fizza; Patini, Romeo; O’Reilly, Lorraine; McCullough, Michael; Celentano, Antonio (Frontiers in Oral Health, 2024)
BackgroundAnticoagulants, renowned for their role in preventing blood clot formation, have captivated researchers’ attention for the exploitation of their potential to inhibit cancer in pre-clinical models.ObjectivesTo undertake a systematic review and meta-analysis of the effects of anticoagulants in murine cancer research models. Further, to present a reference tool for anticoagulant therapeutic modalities relating to future animal pre-clinical models of cancer and their translation into the clinic.MethodsFour databases were utilized including Medline (Ovid), Embase (Ovid), Web of science, and Scopus databases. We included studies relating to any cancer conducted in murine models that assessed the effect of traditional anticoagulants (heparin and its derivatives and warfarin) and newer oral anticoagulants on cancer.ResultsA total of 6,158 articles were identified in an initial multi-database search. A total of 157 records were finally included for data extraction. Studies on heparin species and warfarin demonstrated statistically significant results in favour of tumour growth and metastasis inhibition.ConclusionOur findings constitute a valuable reference guide for the application of anticoagulants in cancer research and explore the promising utilization of non-anticoagulants heparin in preclinical cancer research.Systematic Review RegistrationPROSPERO [CRD42024555603].